2012
DOI: 10.1016/j.jpeds.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Disease Activity, Proteinuria, and Vitamin D Status in Children with Systemic Lupus Erythematosus and Juvenile Dermatomyositis

Abstract: Objective To evaluate relationships between vitamin D, proteinuria, and disease activity in pediatric systemic lupus erythematosus (SLE) and juvenile dermatomyositis (JDM). Study design Multiple linear regression was used to associate subject-reported race, sunscreen use, and vitamin D intake with physician-assessed disease activity and serum 25-hydroxyvitamin D [25(OH)D] in subjects with pediatric SLE (n = 37) or JDM (n = 21). Serum 25(OH)D was correlated with urinary vitamin D binding protein/creatinine ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 34 publications
3
57
0
5
Order By: Relevance
“…Thus the immunomodulating effects of vitamin D may explain the reported epidemiological associations between vitamin D status and a large number of autoimmune and inflammatory diseases [100]. Several reviews [101,102] have shown a high prevalence of vitamin D deficiency in patients with SLE, showing evidence of antibodies to 1,25 (OH) 2 D, the biologically active form of vitamin D, which is rarely measured in clinical practice [103,104]. Mok et al have suggested that 25-(OH)D levels are as specific as antibodies to C1q complement factor (anti-C1q) for detecting concurrent renal activity in SLE and Wu et al [105] have correlated vitamin D levels with CV risk factors [106].…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…Thus the immunomodulating effects of vitamin D may explain the reported epidemiological associations between vitamin D status and a large number of autoimmune and inflammatory diseases [100]. Several reviews [101,102] have shown a high prevalence of vitamin D deficiency in patients with SLE, showing evidence of antibodies to 1,25 (OH) 2 D, the biologically active form of vitamin D, which is rarely measured in clinical practice [103,104]. Mok et al have suggested that 25-(OH)D levels are as specific as antibodies to C1q complement factor (anti-C1q) for detecting concurrent renal activity in SLE and Wu et al [105] have correlated vitamin D levels with CV risk factors [106].…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…They also found no association between disease activity and serum 25-(OH)D levels, which could be explained the fact that the tool they used to measure disease activity was based only on the attending physician's assessment. Moreover, Robinson et al 20 found that vitamin D levels were lower in patients with SLE who had proteinuria than in those who did not have this condition (11.9 and 25.0 ng/ml, respectively). Moreover, they also determined that vitamin D levels were associated with disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Al evaluar las concentraciones de vitamina D se encontró que los sujetos que usan bloqueador solar presentan concentraciones más bajas comparados con aquellos que no lo usan (p = 0.05). En el estudio realizado por Robinson y colaboradores, en el cual evaluaron a 37 sujetos de 4 a 21 años de edad con diagnóstico de LES, reportaron el uso de bloqueador solar en el 57%, que estuvo asociado con un incremento de 6 ng/ml en las concentraciones de 25(OH) D. Cabe mencionar que los usuarios de bloqueador solar fueron los sujetos con ingesta de suplementos de vitamina D, a diferencia de este estudio en el cual los sujetos no tomaron estos suplementos 37 . Se ha descrito en la literatura que el uso de esteroides puede contribuir de forma adversa con el metabolismo y la biodisponibilidad de la vitamina D 6,29 .…”
Section: Discussionunclassified